2015
DOI: 10.1016/j.pnpbp.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Adverse performance effects of acute lorazepam administration in elderly long-term users: Pharmacokinetic and clinical predictors

Abstract: Background The benzodiazepine lorazepam is widely utilized in the treatment of elderly individuals with anxiety disorders and related conditions. Negative effects of acute lorazepam administration on cognitive performance, especially memory, have been reported in both previously untreated elderly and in individuals who have received short term (up to three weeks) treatment with therapeutic doses. However, it remains unclear if these adverse cognitive effects also persist after long-term use, which is frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Ten studies compared neurocognitive and/or driving performance of long-term users to other patient groups [22][23][24], to healthy controls [25][26][27], or to both [28][29][30][31]. Three studies assessed the influence of acute benzodiazepine administration on neurocognitive and/or driving performance of long-term users in comparison to the acute effects of a benzodiazepine in treatment naïve controls [32], placebo [33], or both [34]. Most studies included patients that had been using benzodiazepines for a number of years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies compared neurocognitive and/or driving performance of long-term users to other patient groups [22][23][24], to healthy controls [25][26][27], or to both [28][29][30][31]. Three studies assessed the influence of acute benzodiazepine administration on neurocognitive and/or driving performance of long-term users in comparison to the acute effects of a benzodiazepine in treatment naïve controls [32], placebo [33], or both [34]. Most studies included patients that had been using benzodiazepines for a number of years.…”
Section: Resultsmentioning
confidence: 99%
“…Review Thieme after zopiclone administration, but this effect was not observed in chronic users. Pomara et al [33] examined the effects of a single dose of lorazepam in elderly long-term users of lorazepam. The lorazepam dose was calibrated for each individual participant and based on the highest daily dose of lorazepam.…”
Section: Experimental Studies Of Acute Benzodiazepine Administration mentioning
confidence: 99%
“…Of course this observation would not be of clinical relevance if diazepam was used for a short time, as indicated for all benzodiazepines, but actually a number of surveys suggest that their use is more extensive; in particular, from 13 to 25% of subjects with more than 65 years chronically take them as hypnotic agents [31, 32]. Therefore, it is of great interest to know their cardiovascular effects particularly in subjects bearing a major risk of cardiovascular events such as diabetic, hypertensive and elderly patients as well as in those with cardiac diseases, as compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids can cause central and obstructive sleep apneas (1921), and benzodiazepines contribute to respiratory depression and airway relaxation (22). Benzodiazepines also impair psychomotor function and recall (23), which could mediate the recognized risk for delirium and falls in the hospital (24, 25). These findings suggest pathways by which these medications might contribute to clinical deterioration.…”
Section: Introductionmentioning
confidence: 99%